The ability of administrative leaderships in decision-making and its relationship to the success of the Faculties of Physical Education and Sports Science - أ.د عماد عزيز نشمي أ.د أسعد طارق أحمد أ .د خالد اسود لايخ (physical education and sport sciences college for women/ Baghdad University, 2021)
The study problem crystallized by research and analysis in order to improve and develop the performance of one of the sports institutions, namely the Faculties of Physical Education and Sports Sciences. The objectives of the research included: Building a scale for evaluating senior administrative leaders (administrative officials) in the Faculties of Physical Education and Sports Sciences (Dean, Associate Dean, Branch Head) on decision-making. Identifying the level of ability of senior administrative leaders (administrative officials) on decision-making. The researchers used the descriptive approach. In the survey method, the research community was identified with workers in the Faculties of Physical Education and Sports Sciences concerned with Iraqi universities in the Middle Euphrates and workers in Faculties of Physical Education and Sports Sciences in the universities of the governorates (Babil, Karbala, Najaf, and Qadisiyah) from the dean of the college to the youngest employee in it. Obtaining data The researchers concluded that there is supervision over the teaching staff's time and continuous follow-up by the administrative leaderships in the colleges, and the suggestion of punishments is what it deems appropriate against those who violate them to the dean of the college.